2017
DOI: 10.1038/sc.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the mean arterial pressure and timing of surgical decompression in traumatic spinal cord injury: a retrospective study

Abstract: Our data demonstrated that there may be improved neurologic outcomes in patients with SCI who undergo early surgical decompression. Maintenance of MAP ⩾85 mm Hg for 5 consecutive days post-SCI was also associated with higher rates of AIS grade improvement at mean 26.7 days without a statistically significance difference at prolonged follow-up although a higher rate of neurological recovery persisted in patients with MAP ⩾85 mm Hg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 39 publications
0
44
0
2
Order By: Relevance
“…Dakson et al 11 retrospectively reviewed 94 patients who presented with SCI between 2006 and 2010. Serial hourly MAPs were collected for 50 of these patients.…”
Section: Relationship Of Map Goals To Outcomesmentioning
confidence: 99%
“…Dakson et al 11 retrospectively reviewed 94 patients who presented with SCI between 2006 and 2010. Serial hourly MAPs were collected for 50 of these patients.…”
Section: Relationship Of Map Goals To Outcomesmentioning
confidence: 99%
“…31 Long standing human literature similarly supports maintenance of MAP at about 85 mm Hg for 5-7 days after traumatic spinal cord injury to minimize ischemia and/or additional secondary injury. [32][33][34] Intraoperative MAP was purposefully maintained at a minimum of 80-90 mm Hg throughout surgery in this dog by the use of pressors, and postoperative neurological deterioration was minor and transient. Intraoperative hypotension during ventral slot was associated with 23 times greater likelihood of a postoperative adverse event in dogs.…”
Section: Discussionmentioning
confidence: 96%
“…21 While some studies recommend MAP maintenance for at least 7 days post-injury, others have demonstrated improved neurologic recovery with just 5 days of MAP maintenance. [23][24][25] However, persistently elevated blood pressure has multiple effects and can amplify edema through the injured blood-brain barrier. 21 A weakness of relying solely on MAP is a lack of means to directly calculate the tissue resistance to perfusion.…”
Section: Pathophysiology Newly Injured Patientsmentioning
confidence: 99%